PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI PADA MATERI ASAM BASA DI SMA NEGERI 3 KENDARI - Hardian; Saefuddin; Marhadi, Muh Alim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The difficulty of class XI students of SMAN 3 Kendari in understanding abstract and calculative acid-base material causes low learning outcomes with an average daily test of 68, below the KKM of 75. This study aims to describe the profile of student learning outcomes, measure the effectiveness of the discovery learning model, and analyze student responses to the model. The research method used is a quantitative quasi-experimental type with a control group pretest posttest design. The sample was selected by purposive sampling, consisting of Class XI.3 as the experimental class (n = 32) using the discovery learning model and Class XI.4 as the control class (n = 32) using the direct learning model. Data were collected through objective test instruments, response questionnaires, and activity observation sheets, then analyzed using descriptive and inferential statistics. The results showed that the average posttest score of the experimental class reached 84.84 with a classical completeness of 90%, far surpassing the control class which only achieved an average of 73.59 with a classical completeness of 54%. Normalized Gain (N-Gain) analysis proved that the experimental class's learning outcomes increased by 76.31% (effective category), while the control class's increased by 56.18% (quite effective category). The independent sample t-test showed a significant difference in the average learning outcomes between the two classes (p < 0.001). In addition, the average student activity reached 88.23% and the student satisfaction response was 77.58%, both of which were categorized as very good. In conclusion, the application of the discovery learning model was significantly effective in boosting students' cognitive learning outcomes in acid-base material.